The educational function of the teacher-student relationship. Experiences of a work in progress - Giachery, Gianluca (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
The educational function of the teacher-student relationship. Experiences of a work in progress. The question of the teacher-student relationship is crucial in understanding the complex educational process inside the teaching institution. The approaches a teacher puts into effect in his/her relationship both with the whole group and the single student differ as well as the problems he/she can find either in the mere running of the class or in establishing non-authoritarian learning methods. In that respect, the essay is intended to be the story of the problematizing path started together with the group of the teachers in training and focused on some key-words which held the entire process together: the presentation of the teacher’s role; the relationship with “the difficult boy”; the experience of people who are teachers; meaning and sense of teaching programs. It has emerged a true phenomenology of the roles which brought the irreducible singularity and unicity of being a teacher to light.